Komunіsticzna nomienkłatura jak czinnik pogliblennia jekonomіcznoї krizi u Galiczinі pierіodu pieriebudowi - Chura, Vasyl (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2019)
Among the key causes of the collapse of the Soviet Union, the Council for Mutual Economic Assistance and the Treaty of Warsaw were socio-economic factors, which were at the forefront and were based on the total incompetence of the communist leadership in production matters. The party nomenclature constantly replaced the activities of the economic structures of the country, ignorantly dictated plans and vectors of development that ultimately led to a permanently low material living standards of the citizens of the USSR and a permanent production shortage. It reached its peak in the late 80s of the 20th century, turned into a total crisis and set the country on the brink of failure. As a result, the socio-economic problems in the synthesis with a quantity of political, ethnic and religious issues significantly intensified the national liberation movement and led to the restoration of the state independence of Ukraine, collapse of the USSR and the alliances imposed by the Soviet Union on satellite countries.(original abstract)